IDENTIFIKASI PARASIT YANG MENYERANG IKAN MAS KOKI (Carassius auratus) DI KABUPATEN LOMBOK BARAT - Sumahiradewi, Luh Gede; Winasari, Hesti; Sulystyaningsih, Naning Dwi; Hamid; Nufus, Chairun (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Goldfish (Carassius auratus) is one of the most popular ornamental fish and is in great demand by the public. In addition, this fish is easy to cultivate and has high economic value. One of the challenges faced by cultivators is quality loss caused by parasitic attacks. This study aims to determine the type, prevalence and intensity of parasites that attack goldfish so that appropriate countermeasures against parasitic attack Luh Gede Sumahiradewi s can be identified. This study uses a survey method. The primary data collected included length and weight of fish, type and number of parasites, and water quality (temperature, pH, DO and ammonia). Goldfish taken from three cultivation locations in West Lombok Regency (Langko Village, Duman and Embungpas) obtained 15 samples. The results showed that five types of parasites were found attacking goldfish samples, namely Argulus sp., Trichodina sp., Chillodonella sp., Gyrodactylus sp. and Dactylogyrus sp. The parasite prevalence rates obtained ranged from 40 – 100% with the general to always category. The parasite intensity values obtained ranged from 2 – 31 individuals/head with low to moderate categories. As for the water quality parameters during the study, temperature ranged from 21 – 23 oC, pH ranged from 6 – 7, DO 5 – 8 mg/L and ammonia 0.01 mg/L.